HUBUNGAN KARAKTER DISIPLIN DAN TANGGUNG JAWAB TERHADAP NILAI AKHIR MAHASISWA CALON GURU (Studi pada Mahasiswa Pendidikan Jasmani Kesehatan dan Rekreasi FKIP Unsyiah dan Mahasiswa PendidikanBiologi FTK UIN Ar-Raniry) - Masri Masri; Eva Nauli Taib (Universitas Islam Negeri Ar-Raniry, 2019)
The purpose of this study is to determine the relationship between the discipline and responsibility to the student's final grade. This study is an ex post facto research with population of Physical and Health Education students. The sample number is 100 students using a purposive sampling technique. The data was analyzed using the correlation and regression formula. The results of data analyzing is that r1 = 0.87, r2 = 0.4, R1 = 0.67, r3 = 0.68, r4 = 0.79 and R2 = 0.77. It can be concluded that there is a significant relationship between the discipline and the responsibilities towards the final grades of the Physical and Health Education students.